PyBacktrack 1.0: A Tool for Reconstructing Paleobathymetry on Oceanic and Continental Crust. (22nd June 2018) - Müller, R. D.; Cannon, J.; Williams, S.; Dutkiewicz, A.
Abstract: ThepyBacktrack software package allows the backtracking of the paleo‐water depth of ocean drill sites, providing a framework for reconstructing the accumulation history of sediment components through time. The software incorporates the effects of decompaction of common marine lithologies and allows backtracking of sites on both oceanic and continental crust. Backtracking on ocean crust is based on a user‐selected lithospheric age‐depth model and the present‐day unloaded basement depth. Backtracking on continental crust is based on syn‐rift and post‐rift subsidence that is modeled using the total sediment thickness at the site and the timing of the transition from rifting to thermal subsidence. On sites that did not penetrate basement, the age‐coded stratigraphy is supplemented with a synthetic stratigraphic section that represents the undrilled section, whose thickness is estimated using a global sediment thickness map. This is essential for estimating the decompacted thickness of the total sedimentary section, and thus bathymetry, through time.PyBacktrack further allows the consideration of the effects of mantle‐convection driven dynamic topography on paleo‐water depth. The user can select one of the dynamic topography models bundled withpyBacktrack or add other models.PyBacktrack runs on all platforms with a Python 2.7 and apyGPlates installation and is available via Github. Key Points: ThepyBacktrack software package allows the reconstruction of the paleo‐water depth of ocean drill sites through time The software incorporates the effects of decompaction of key lithologies and allows backtracking of sites on oceanic and continental crust PyBacktrack considers the effects of mantle convection driven dynamic topography on paleo‐water depth